A study of marketing strategy on foods and beverages industry in Klang Valley / Siti Aida Ahmad - Ahmad, Siti Aida (2005)
This research is to study the effectiveness of marketing strategy used on Foods and Beverages manufacturing business in Klang Valley. It contains 5 topics. This study is completed after a research has taken place in the period of four month. Chapter one is the introduction of study as a whole. It contains the background of study on Foods and Beverages Industry in Klang Valley. Many food and beverage products, which are being processed by small-scale entrepreneurs, are highly acceptable by consumers. This chapter also provides the problems and the reasons of selecting the field. These products have potential to expand their market size, especially if there are improvements in product quality and level of technology. Advances in processing technology have widened the usage of local raw materials, expanding the range of products and increasing the investment absorbing capacity in the food and beverage industry. The significant of study done since lifestyle changes have led to an increase in the demand for convenience foods and drinks, and health foods and drinks. Scope of the study for food and beverage products involve the general marketing approaches and techniques applied the marketing of other kinds of products and services. It considered about marketing orientation, new product development, competitive / SWOT analysis and Research and Development (R&D) that should be used in developing marketing strategy for food and beverage manufacturing companies. Theoretical framework is also included for establishing the theory of marketing strategy by viewing the dependent variable and independent variables for the study. Chapter two is the literature review of this study. The supporting matter of the study is explained in this chapter which refers to few articles, journals and books. This chapter also described the important of marketing strategy used on this industry. Through this chapter will emphasize finding breakthrough opportunities that help innovators develop hard-to-copy marketing strategies that will be very profitable for a long time. Literature review lighted some of the techniques involved in the preparation of finding and analysis. It is none other than a systematic and thorough search of published literature in order to identify as many items as possible on this topic. The idea is to become familiar with all the existing information about the foods and beverages industry phenomenon with the idea of marketing strategy theories, and the process is best begun shortly after a research idea is develop. There are some theory explanations about the scope of study of this research. Literature review includes the theory of analyzing marketing opportunities, SWOT analysis and relationship marketing which are the important parts in this fieldwork. It also includes the Research and Development (R&D) issue and theory. Chapter three focuses on the research methodology and design of the study. The data collection methods in this chapter will explain why it is needed. Primary data is the method used in this study. It is originated by a researcher for specific purpose of addressing the problem at hand. The reason of choosing the sampling techniques of this study is also self-explanatory in this chapter. Although sampling is common place in daily activities, most of these familiar samples are not scientific. The concept of sampling may seem simple and intuitive, but the actual process of sampling can be quite complex. Sampling is a central aspect of marketing research, and it requires in-depth examination. Chapter three also contains data analysis techniques, research budget and work schedule.